Fast-Track Data Monetization With Strategic Data Assets - Wixom, Barbara; Wixom, Barbara; Piccoli, Gabriele; Rodriguez, Joaquin (MIT Sloan Management Review, 2021)
Unlike traditional company assets that will deteriorate or be depleted over time, data can be reused and recombined freely without degradation. Increasing the liquidity -- the ease of data asset reuse and recombination -- of strategic data is the first step to data monetization. The authors describe how the efforts of a financial services firm and three other organizations to facilitate the recurring reuse and recombination of strategic data assets are paying off.